Prenatal sonographic evaluation of Arnold Chiari II Malformation - Raghu T, Sadineni; Kumar B, Santh; kumar K, Praful; K., Chandra Sekhar; BN, Chander; Boppana Mahita, Durga (International Journal of Medical Research and Review, 2017)
Arnold Chiari malformations are a broad group of malformations with distinctive imaging findings. They are named after an Austrian pathologist Hans Chiari who first identified types I-III in 1891. It is a spectrum of congenital abnormalities of CNS, characterized by downward displacement of the parts of the cerebellum, fourth ventricle, pons and medulla oblongata into the spinal canal. Type II is the most common subtype and is invariably associated with open neural tube defects like myelomeningocele. They constitute an important cause of neonatal morbidity and mortality and hence the need for prenatal evaluation with ultrasound to detect the anomalies. In this article we describe the features of Arnold chiari malformation, illustrate type II cases with sonological parameters for assessment, discuss the findings for diagnosis and conclude with prognosis and management.